PENGELOLAAN DAYA TARIK WISATA DI OBJEK WISATA PANTAI AIR MANIH - Renato, Valdo; Waryono, Waryono; Abrian, Youmil (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This research is motivated by the Objek Wisata Pantai Air Manih are managed poorly, visible from traveler ratings and the public on the management of a tourist attraction less well categorized. This study aimed to describe: (a) planning, (b) organizing, (c) directing, and (d) supervision Tourist Attractions the Objek Wisata Pantai Air Manih. The results showed that the management of tourist attraction in the attractions Pantai Air Manih still limited in environmental management level manager. For the next plan of long-term planning as a marine tourism and short term to increase the number of tourists, the organizing manager of coordination but is still limited to oral and written, while briefing the manager at the attraction waiting for instructions from the department and on the supervision, management oversight carefully and remind each respective task management officers in the field.Keywords: Management, Tourist Attractions.